Respuesta :
Answer:
Y = (-3) *X - 10
solution for Y =0 ---> X = -10/3
Step-by-step explanation:
Two points:
(Y0 ; X0) = (-4 ; 2)
(Y1 ; X1) = (-2 ; -4)
There is only one line which pass for both of them, his general expresion is:
y = a*x + b --- (1)
Calculating "a": is the pending of the line.
[tex]a = \frac{Y1 - Y0}{X1 - X0} = \frac{(-4) - (2)}{-2 - (-4)} =\frac{-6}{2} = -3[/tex]
Calculating "b":
Since every point who belongs to the line satisfied the (1) expresion, we can use it for the point (Y1 ; X1) :
[tex]Y0 = (-3)*X0 + b ---> 2 = (-3)*(-4) + b ---> b = -10[/tex]
Final expresion
Replacing in (1): [tex]Y = (-3) *X - 10[/tex]
Solutions: [tex]Y = (-3) *X - 10 = 0 --- > X = -\frac{10}{3}[/tex]
Answer:
The 2nd and last one
Step-by-step explanation:
(-2,-4)
(-5,5)
I did it on edge 2020